EFEKTIVITAS KOMBINASI BRAIN GYM DAN MATCHING CARD GAME TERHADAP PENINGKATAN FUNGSI KOGNITIF PADA LANSIA - Pramono Pramono; Pramono Giri Kriswoyo; Moh Ridwan; Erna Erawati (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2026)
Cognitive decline in older adults is a serious issue that increases the risk of dementia and reduces independence and quality of life. Dementia, particularly Alzheimer's disease, is the most common type, with risk factors including age, genetics, hypertension, and diabetes. Brain gym and matching card game therapies are known to stimulate cognitive abilities; however, their combined effect has not been widely studied. This study aimed to determine the effectiveness of combining brain gym and matching card game interventions in improving cognitive function among older adults. This research employed a quantitative pre-experimental design with a one-group pretest–posttest approach. A total of 35 older adults were selected using purposive sampling based on inclusion criteria. Cognitive function was measured using the Mini Mental State Examination (MMSE) and analyzed using the Wilcoxon test to assess differences before and after the intervention. Respondent characteristics showed that 77% were aged 60–74 years, 83% were female, and 54% had elementary school education. The results indicated a significant difference in cognitive function scores before and after the combined brain gym and matching card game intervention (p value = 0.00). The combination of these two therapies was proven to significantly improve cognitive function in older adults and may serve as an effective strategy to maintain cognitive health and enhance their overall well-being.